A Review of Cross Border Higher Education in Africa: Focus on Graduate Level Training in Engineering and Technology - N, Banadda; I. N, Oteyo; P, Nampala; E, Dintwa; E, Adipala (International Journal of Sustainable Development & World Policy, 2017)
Cross border education has become part of the options for higher education in countries with inadequate education opportunities. This is based on the fact that education is one of the pillar for economic development and improved living standards. Thus, many nationals from different African countries are taking higher education seriously and are seeking every available opportunity to pursue it. Consequently, this translates to an ever increasing demand for higher education in the continent. Cross border higher education has potential to meet this growing demand and provide more opportunities that can be leveraged to meet the engineering threshold for Africa and provide home grown technological solutions. This paper was motivated by the Mobility for Engineering and Technology Graduates (METEGA) in Africa and similar projects that have seen students move to other countries in the continent for graduate training. The paper presents a review of cross border higher education with a focus on graduate level training in engineering and technology.